Growth and early laying performance of a broiler parent stock in an open-sided house under restricted feeding - Rahman, MR; Chowdhury, SD; Hossain, ME; Ahammed, M (Bangladesh Journal of Animal Science, 2015)
An experiment was carried out with SHAVER Starbro broiler parent stock from one day old to the point of peak production to investigate the growth, early laying performance and their adaptability during brooding, growing and early laying periods. The experimental period was divided into five phases, phase I (0 2nd week), phase II (3rd 8th week), phase III (9th 22nd week), phase IV (23rd sexual maturity), phase V (sexual maturity to peak production). The experiment was carried out in an open sided house and management practices of birds were close to the recommendation of the broiler breeder. It may be concluded that it is possible to achieve standard body weight of SHAVER Starbro broiler parent stock under Bangladesh condition even sometimes with lower amounts of feed allocations as specified by breeder. The birds reach sexual maturity at 31st week, later than the breeders standard (23rd week) and the persistency in peak production is shorter but egg weight ranges from 53g to 60g, suitable for hatching. Mycoplasmosis appears to be major health problem, affecting performance. Use of sand is not suitable as a litter material for the management, as the birds consume a lot of sand under restricted feeding program. It may be suggested that SHAVER Starbro broiler parent stock could be reared under Bangladesh condition for the production of hatching eggs. DOI: http://dx.doi.org/10.3329/bjas.v44i1.23141 Bang. J. Anim. Sci. 2014. 44 (1): 40-45